Fabrication and Characterization of Soframycin-Loaded Carboxymethyl Tamarind Gum-Guar Gum Hydrogel Films: Soframycin loaded hydrogel films - Ghorpade, Vishwajeet Sampatrao; Mali, Kailas Krishnat; Havaldar, Vijay Daulatrao; Shikalkar, Afroj Usman; Varude, Om Santosh; Dias, Remeth Jacky (Iranian Journal of Pharmaceutical Sciences, 2026)
Hydrogel films fabricated solely from citric acid (CA)-crosslinked carboxymethyl tamarind gum (CMTG) often suffer from poor matrix integrity and limited swelling capacity, hindering their practical utility in drug delivery and other biomedical applications. To address these challenges, this study developed hydrogel films by blending CMTG with guar gum (GG) and crosslinking with citric acid, aiming to enhance the films’ matrix integrity and swelling behavior substantially. The hydrogel films were loaded with soframycin via diffusion. The fabricated films were evaluated for various parameters, including weight loss, thickness, total carboxyl content, wettability, permeability, protein adsorption, and hemocompatibility. The swellability of the films was studied in Tris-HCl buffer (pH 7.4) and 0.1 N HCl. In addition, drug release studies were conducted in Tris-HCl buffer (pH 7.4). The films were characterized using ATR-FTIR spectroscopy and thermal analysis. The findings revealed that the concentrations of GG and CA affected the weight loss, thickness, total carboxyl content, and contact angle. The swelling of CMTG-GG hydrogel films was found to be greater than that of previously reported CMTG-PVA films. The fabricated films exhibited optimum water vapor transmission and microbial impermeability. Protein adsorption on the hydrogel films remained minimal. Additionally, the hemolysis percentage remained below the accepted limit of 5 %, confirming that the hydrogel films were compatible with blood. The ATR-FTIR analysis confirmed the crosslinking. The drug release from the soframycin-loaded hydrogel films was found to be 39.1 % to 79.69 % at the end of 6 h. The drug release from these hydrogel films followed a non-Fickian diffusion mechanism. These findings suggest that hydrogel films composed of CMTG and GG have promising potential for drug delivery.